Moral Reforms in a Community: Modus Operandi in the Light of Sīrah - Muhammad Khubaib; Muhammad Umair (Journal of Islamic and Religious Studies, 2019)
It’s always the people who define the status of a society. If the people of a society are civilized, the society will be called an ideal society. Moral reforms and behavioural therapy of individuals of the society are basic factors to establish an ideal society. Such an ideal society was established by Prophet Muḥammad (P.B.U.H) in Madina where he laid the foundations of brotherhood and equality among citizens of that state. He showed tolerance towards people belonging to different religions by protecting all their human rights and by providing indiscriminate and quick justice. He not only made the social institutions strong but also developed a history of human civilization. We simply need to work on our moral values and behaviours. We should study the daily life of Muḥammad (P.B.U.H) and mould our lives according to that. Dire need of the modern world is the rectification of human behavior in the light of the ideal life of Muḥammad (P.B.U.H). It will give an opportunity to breathe the same spirit into the contemporary social attitudes so that our society may become peaceful.